Pengaruh Keunikan Produk, Harga dan Sosial Media Marketing terhadap Keputusan Pembelian pada UMKM ASDG Ikat Art Maumere - Maria Mistela Yuvika; I Nengah Wirsa (Lembaga Pengembangan Kinerja Dosen, 2026)
This study seeks to investigate the influence of product uniqueness, price, and social media marketing on purchasing decisions at ASDG Ikat Art Maumere MSMEs. A quantitative approach was adopted using a survey method involving 85 respondents who were consumers of ikat weaving products. Respondents were selected through purposive sampling. Data were obtained using Likert-scale questionnaires and analyzed through multiple linear regression with SPSS. The findings reveal that, individually, product uniqueness has a positive and significant effect on purchasing decisions (sig. 0.017), price also shows a positive and significant influence (sig. 0.006), and social media marketing similarly exerts a positive and significant impact (sig. 0.030). Simultaneously, all three variables significantly affect purchasing decisions, as indicated by an F-value of 44.049 with a significance level of 0.000. The Adjusted R² value of 0.606 indicates that 60.6% of the variance in purchasing decisions is explained by product uniqueness, price, and social media marketing, while the remaining proportion is attributed to other factors beyond the research framework. These results suggest that distinctive motifs and cultural values embedded in ikat weaving, appropriate pricing aligned with product quality, and effective implementation of social media marketing play a vital role in strengthening consumer purchasing decisions. Therefore, ASDG Ikat Art Maumere MSMEs are encouraged to continuously enhance product differentiation, apply competitive pricing strategies, and optimize social media-based marketing efforts to improve competitiveness and ensure business sustainability.